The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ange.202207824
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Radical NHC Catalysis: Divergent Difunctionalization of Olefins through Intermolecular Hydrogen Atom Transfer

Abstract: Oxidative N-heterocyclic carbene (NHC) organocatalysis, typically leading to the formation of acyl azolium reactive intermediates, constitutes one of the most important activation strategies for the NHCcatalyzed chemical transformations. Here, we report an unprecedented oxidative radical NHC catalysis by using peroxyester as the external single-electron oxidant to realize divergent difunctionalization of olefins. The key to success of this chemistry is the catalytic generation of oxygen radicals that could tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Recent efforts from Li's group revealed that peroxyesters could also act as oxidants and intermolecular hydron atom initiators in the NHC catalytic system. 56 The reaction of vinylarenes and aldehydes in the presence of peroxyester as oxidant and Cs 2 CO 3 (1.5 equiv.) as base in DMSO at 60 °C could produce a collection of 1,4-diketones (Scheme 30).…”
Section: Radical Acylation Of Alkenesmentioning
confidence: 99%
“…Recent efforts from Li's group revealed that peroxyesters could also act as oxidants and intermolecular hydron atom initiators in the NHC catalytic system. 56 The reaction of vinylarenes and aldehydes in the presence of peroxyester as oxidant and Cs 2 CO 3 (1.5 equiv.) as base in DMSO at 60 °C could produce a collection of 1,4-diketones (Scheme 30).…”
Section: Radical Acylation Of Alkenesmentioning
confidence: 99%
“…N-heterocyclic carbenes (NHCs) 9 could stabilize acyl radicals 10 and open a new avenue for single-electron-transfer (SET)-mediated radical acylation chemistry. 11 Since the pioneering works of Studer 12 and Ohmiya, 13 a elegant progress has been achieved in NHC-involved cross-couplings of ketyl radicals with O-centered radicals, 12 alkyl radicals, 13–18 and highly active allene radicals 19 by employing aldehydes or derivatives of carboxylic acid (Scheme 1b). The attachment of NHCs could modulate the stability of transient acyl radicals to persistent ones, which may offer the opportunity for radical acylation of allyl radicals.…”
Section: Introductionmentioning
confidence: 99%